Stereoselective Synthesis of Hydropyrano[3, 2‐b]indoles via Organocatalytic Asymmetric Inverse‐Electron‐Demand Oxa‐Diels–Alder Reaction. Issue 18 (3rd August 2016) - Yang, Lei; Huang, Wei; He, Xiang‐Hong; Yang, Ming‐Cheng; Li, Xiang; He, Gu; Peng, Cheng; Han, Bo
Abstract: Enantio‐ and diastereoselective inverse‐electron‐demand oxa‐Diels–Alder reactions are described between ( Z )‐2‐ylideneoxindoles and aldehydes in the presence of a chiral secondary amine catalyst. The corresponding hydropyrano[3, 2‐ b ]indoles are produced in up to 77% yield with up to 99% ee . Convenient synthetic transformations of the products readily lead to pharmacologically interesting scaffolds bearing multiple functional groups. This method may also provide an alternative approach for the asymmetric synthesis of 2‐spirocyclo‐3‐oxindoles. Abstract :